Study on Lactiplantibacillus plantarum R6-3 from Sayram Ketteki to prevent chronic unpredictable mild stress-induced depression in mice through the microbiota–gut–brain axis. Issue 7 (20th March 2023) - Zhao, Lina; Li, Dongyao; Chitrakar, Bimal; Li, Chen; Zhang, Na; Zhang, Shaogang; Wang, Xinyu; Wang, Miaoshu; Tian, Hongtao; Luo, Yunbo
Abstract : Through microbiota–gut–brain axis, L. plantarum R6-3 improved intestine SCFAs, monoamine neurotransmitter, BDNF, HPA axis, immune and oxidative stress through regulating gut microbiota, thereby preventing CUMS-induced depression behavior in mice. Abstract : The prevention, mitigation and treatment of depression has become a global issue that needs to be solved urgently. Sayram Ketteki, a traditional natural fermented yoghurt from the region with the world's fourth highest life expectancy, has been known as the "longevity secret", whose longevity and anti-depression factors are speculated to come from its rich microorganisms. Therefore, for the first time, we systematically studied in depth the microbes of Sayram Ketteki, screened a new edible probiotic strain, Lactiplantibacillus plantarum R6-3, and explored its anti-depression effect in chronic unpredictable mild stress (CUMS)-induced depression in mice. It is encouraging that L. plantarum R6-3 was significantly superior to the classic anti-depressant drug, fluoxetine, in the performance of promoting sucrose preference test (SPT) behavior by 18% ( p < 0.001), lowering the serum CORT content by 5.6% ( p < 0.05), accelerating the brain-derived neurotrophic factor (BDNF) level by 5.9% ( p < 0.01), increasing the serum IL-10 concentration by 2.3% ( p < 0.05), up-regulating the expression of BDNF and phosphorylated-ERK by 74% ( p < 0.01) and 45% ( p < 0.001), respectively, and facilitating the secretion of fecal short-chain fatty acids (SCFAs), including n -butyric, n -valeric, and isovaleric acid by 47% ( p < 0.01), 42% ( p < 0.05) and 38% ( p < 0.05), respectively. Through the microbiota–gut–brain axis, L. plantarum R6-3 promoted the secretion of intestinal SCFAs through regulation of the composition and function of the gut microbiota, and activated the production of the monoamine neurotransmitter, renewed the level of brain neurotrophic factor, and suppressed the hyperactivity of the hypothalamic–pituitary–adrenal (HPA) axis by adjusting the hippocampal BDNF/TrkB/ERK/CREB signaling pathway, thereby improving the immune and oxidative stress status, protecting hippocampal tissue from damage, maintaining a healthy weight and preventing CUMS-induced depressive behavior in mice. It has great prospects for the development of natural functional foods, the prevention and treatment of depression and in innovative microecological preparations.